The Brazilian version of the High-Activity Arthroplasty Score: psychometric property evaluation in hip replacement patients - Nathalia Sundin Palmeira de Oliveira; Julia Ribeiro Soares; Danúbia da Cunha de Sá Caputo; Gustavo Leporace; Luiz Alberto Batista; Themis Moura Cardinot; Liszt Palmeira de Oliveira (São Paulo Medical Journal)
ABSTRACT BACKGROUND: The High-Activity Arthroplasty Score (HAAS) is a reliable and valid self-administered questionnaire that was developed in British English and was designed to determine the level of physical activity in patients after lower limb arthroplasty (hip and/or knee). The Brazilian version (HAAS-Brazil) was developed after a cross-cultural adaptation in 2023. OBJECTIVE: To evaluate the psychometric properties of HAAS-Brazil in patients after hip arthroplasty. DESIGN AND SETTING: A cross-sectional quantitative and qualitative study was conducted in an orthopedic outpatient setting. METHODS: Evidence for the validity of HAAS-Brazil was assessed via psychometric testing, which followed the COnsensus-based Standards for the selection of health status Measurement INstruments (COSMIN). RESULTS: A total of 112 patients with a mean age of 56 years were included as participants; of these patients, 50.9% were female, with 44.6% being overweight and 85.7% being engaged in physical activity. HAAS-Brazil provided satisfactory evidence of content validity (CVC > 0.9), structural validity (AISP = 1; Hi > 0.3; VIMon = 0; VIIIO = 0), construct validity (ρ HOS-SP = 0.696; ρ SF-12 PSC = 0.554; ρ SF-1 MSC = 0.338), no ceiling or floor effect, acceptable internal consistency (Mokken ρ = 0.707; Cronbach α = 0.663), and good reliability (ICC(3,K) = 0.840 ; P < 0.001). CONCLUSION: The HAAS-Brazil provided satisfactory validation evidence in patients who underwent hip arthroplasty.